Analysis of tuned liquid column damper nonlinearities. (15th September 2018) - Dziedziech, K.; Ghosh, A.; Iwaniec, J.; Basu, B.; Staszewski, W.J.; Uhl, T.
Highlights: Analysis of open and sealed tuned liquid column damper nonlinearities is performed. Mathematical models of the nonlinear behaviour of the damper are presented. Experimental tests are conducted on a full scale model of the damper. Identification procedure, based on wavelet analysis, is performed. The damping ratio is nonlinear, time-variant and depends on the level of vibration. Air pressure in the sealed damper is nonlinear and generates higher odd harmonics. Abstract: Broadband environmental excitations from wind, ocean wave and earthquakes are especially dangerous for flexible tall structures such as wind turbines, towers or cable-stayed bridges. Liquid Dampers have been studied for almost thirty years in terms of their capability for suppression of vibration in such structures. The work presented in this paper focuses on the Tuned Liquid Column Damper, both open and sealed, and the identification of its time-varying properties of nonlinear damping, frequency and air pressure identification. Experimental tests are conducted on a full scale model of the damper which is subjected to both white noise and harmonic excitation by means of a hydraulic shaker. Exponential decay of the displacement of the liquid column was measured and analysed. The identification procedure was conducted step-wise, first, mode separation with the use of Continuous Wavelet Transform was carried out and then identification of the instantaneous damping ratio for the first mode of vibration was performed. Results indicate that the damping ratio is nonlinear, time-varying and depends on the level of vibration. The air pressure data in the sealed TLCD was also recorded and analysed to reveal the nonlinear nature of the pressure change and the presence of higher odd harmonics.